Metallicity evolution of direct collapse black hole hosts: CR7 as a case study. Issue 1 (30th March 2017) - Agarwal, Bhaskar; Johnson, Jarrett L.; Khochfar, Sadegh; Pellegrini, Eric; Rydberg, Claes-Erik; Klessen, Ralf S.; Oesch, Pascal
Abstract: In this study, we focus on the z  ∼ 6.6 Lyman α CR7 consisting of clump A, which is host to a potential direct collapse black hole (DCBH), and two metal-enriched star-forming clumps B and C. In contrast to claims that signatures of metals rule out the existence of DCBHs, we show that metal pollution of A from star-forming clumps B and C is inevitable, and that A can form a DCBH well before its metallicity exceeds the critical threshold of $10^{-5}\text{--}10^{-6}\ \rm Z_{{\odot }}$ . Assuming that metal mixing happens instantaneously, we derive the metallicity of A based on the star formation history of B and C. We find that treating a final accreting BH of 10 6 –10 7  M⊙ in A for nebular emission already pushes its H 160  − [3.6] and [3.6] − [4.5] colours into the 3σ limit of observations. Hence, we show that the presence of metals in DCBH hosts is inevitable, and that it is the coevolution of the Lyman–Werner radiation field and metals originating from neighbouring galaxies that governs DCBH formation in neighbouring initially pristine atomic cooling haloes.